Effect of Curcuma zedoaria Rosc. ethanolic extract on the lung tumor growth on post initiation phase in female mice induced by Benzo(a)pyrene - Retno Murwanti; Edy Meiyanto; Arief Nurrochmad; Susi Ari Kristina (Indonesian Journal of Pharmacy, 2004)
Curcuma zedoaria Rosc. rhizomes has been used as a traditional cancer medicine since a long time ago, but the so far researches performed on the pharmacological mechanism were lacking. This present research has been done to determine the effect of ethanolic extract of Curcuma zedoaria Rosc. rhizomes on lung cancer of female mice previously induced by Benzo[a]pyrene (B[a]P).Newborn mice were induced by B[a]P and then were separated between male and female mice. On 30th day after birth, female mice were given the ethanolic extract of Curcuma zedoaria Rosc. rhizomes and divided into five groups. Three groups were given 200, 500 and 750 mg/kgBB extract, a group was given solvent (DMSO) as negative control, and another group was given nothing as positive control.The results of this present research shown that the ethanolic extract of Curcuma zedoaria Rosc. rhizomes has proved to posses inhibition effect on lung cancer growth in female mice, at dose of 250 mg/kgBB (49,63%), 500 mg/kgBB (73,33%) and 750 mg/kgBB (77,78%).Keywords : Newborn Mice, Benzo[a]piren, Curcuma zedoaria Rosc.